CONTRIBUTIONS OF CENTRAL ASIAN SCHOLARS TO THE DEVELOPMENT OF ISLAMIC SCIENCES: SARAKHSI – FOUNDER-FATHER OF INTERNATIONAL LAW (TSUL LEGAL REPORT, 2026)
This article is dedicated to contributions of Central Asian scholars to the development of islamic sciences, including Muhammad ibn Ahmad Abu Bakr Sarakhsi’s legacy in international law doctrine. Author gives an authoritative statement that Central Asia, namely Uzbekistan, is, apparently, the homeland of International Law thanks to works of formidable scholar Muhammad ibn Ahmad Sarakhsi, so-called as “Hugo Grotius of the Muslims”. According to him, by interpreting Arabic scholar Muhammad Shaybani’s book “Kitab al-Siyar al-Kabir”, Sarakhsi was first to set forth the “Siyar” – “International Law” as an autonomous and legitimate discipline within the framework of law. Author firmly maintains that Sarakhsi was a leading scientific authority who was credited by all islamic scholars as being one of the greatest scholars of Islamic jurisprudence of his time. According to author’s preliminary research results, he was one of the real founder-fathers of international law.